2015
DOI: 10.2527/jas.2015-9562
|View full text |Cite
|
Sign up to set email alerts
|

The developmental transcriptome landscape of bovine skeletal muscle defined by Ribo-Zero ribonucleic acid sequencing1

Abstract: Ribonucleic acid sequencing (RNA-Seq) libraries are normally prepared with oligo(dT) selection of poly(A)+ mRNA, but it depends on intact total RNA samples. Recent studies have described Ribo-Zero technology, a novel method that can capture both poly(A)+ and poly(A)- transcripts from intact or fragmented RNA samples. We report here the first application of Ribo-Zero RNA-Seq for the analysis of the bovine embryonic, neonatal, and adult skeletal muscle whole transcriptome at an unprecedented depth. Overall, 19,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In the present study, three significant expression profiles were identified and combined into two clusters, class I profiles (profiles 1 and 0) with downregulated patterns and a class II profile (profile 6) with an upregulated pattern. According to the results of the STEM software analysis, it was found that there were cases in which genes were downregulated in the class I profiles, for example, PAX7, Col4A1, Col4A2, IGF2R, IGF2, FN1, MYL4, and MYL7, consistent with research on cattle and goats [46,47]. In the class II profile, many upregulated genes were observed, including LMOD2, MUSTN1, XIRP2, PDLIM5, MYF6, and TNNT1, also in accordance with a previous report on cows [47].…”
Section: Kegg Analysis Based On Time-series Expression Profile Clustesupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, three significant expression profiles were identified and combined into two clusters, class I profiles (profiles 1 and 0) with downregulated patterns and a class II profile (profile 6) with an upregulated pattern. According to the results of the STEM software analysis, it was found that there were cases in which genes were downregulated in the class I profiles, for example, PAX7, Col4A1, Col4A2, IGF2R, IGF2, FN1, MYL4, and MYL7, consistent with research on cattle and goats [46,47]. In the class II profile, many upregulated genes were observed, including LMOD2, MUSTN1, XIRP2, PDLIM5, MYF6, and TNNT1, also in accordance with a previous report on cows [47].…”
Section: Kegg Analysis Based On Time-series Expression Profile Clustesupporting
confidence: 74%
“…According to the results of the STEM software analysis, it was found that there were cases in which genes were downregulated in the class I profiles, for example, PAX7, Col4A1, Col4A2, IGF2R, IGF2, FN1, MYL4, and MYL7, consistent with research on cattle and goats [46,47]. In the class II profile, many upregulated genes were observed, including LMOD2, MUSTN1, XIRP2, PDLIM5, MYF6, and TNNT1, also in accordance with a previous report on cows [47]. For instance, many MYL protein family members were found in this study.…”
Section: Kegg Analysis Based On Time-series Expression Profile Clustesupporting
confidence: 74%
“…A transcript represents a mature RNA molecule, and "gene" refers to one or more transcript subtypes of a common exon in a mature cut form. When the transcription factor expression level changes, genes with different subtypes can encode the same protein, which helps maintain the gene expression at a certain level[ 27 ]. In addition, different subtypes of the same gene can also encode different proteins, which may have specific functions in different breeds.…”
Section: Resultsmentioning
confidence: 99%
“…The growth ratio of the longissimus dorsi muscle is relatively more stable than that of other muscles. Thus, a previous study focused on and revealed mRNA or miRNA expression levels in longissimus dorsi muscle using high-throughput RNA-seq analysis of animals during growth and development periods [19,20]. On the other hand, RNA-seq is an efficient way to map and quantify the transcriptome and to analyze differentially expressed genes (DEGs) in different breeds.…”
Section: Introductionmentioning
confidence: 99%